DEL AF FAMILIEN: Penge og gavegivning i danske udvekslingsfamilier - Priskorn, Mia (Tidsskriftet Antropologi, 2004)
This article deals with the financial aspect of kinship and is based on field data collected in Denmark among ‘exchange families’ consisting of Danish host families and foreign exchange students living with the families for up to one year. The theoretical background of the article is the ideal separation between money and family in Western society depicted by the anthropologists Maurice Bloch, David Schneider and James Carrier. The ethnographic material in the article is represented primarily by an extended case, and shows clearly that the separation is ideal, and that family life and finances are inseparable entities. The article analyses one reason why the exchange families are faced with financial challenges: Exchange organizations expect host parents to treat the exchange student as they treat their own child, and Westerners generally expect parents to treat their children in the same way. The article demonstrates that factors such as money and gifts affect the continuous creation of social relatedness in the “exchange families”. However, host parents’ intention of financially treating the exchange student like one of their children is doomed from the very start, since the financial conditions of the exchange student and the host siblings differ fundamentally. This difference challenges both the notion of sibling equality and the ideal relationship between parents as givers and children as receivers.